fNIRS, EEG, ECG, and GSR reveal an effect of complex, dynamically changing environments on cognitive load, affective state, and performance, but not physiological stress - Dybvik, Henrikke; Erichsen, Christian Kuster; Snider, Chris; Steinert, Martin (Frontiers in Human Neuroscience, 2025)
This study used functional near-infrared spectroscopy (fNIRS), electroencephalography (EEG), electrocardiography (ECG), electrodermal activity (EDA), performance, and subjective self-reports to investigate cognitive load and stress in a complex, dynamically changing environment. A total of 30 participants (N = 30) were assigned to three Tetris gameplays: Easy and Hard had constant difficulties, and Ramp started at a low difficulty level before successively ramping up to a very high difficulty level. Participants performed significantly better in Easy, followed by Ramp and Hard. In general, increased workload resulted in increased cognitive load and stress, but only up to a certain threshold, after which fNIRS activation reduced, possibly due to mental fatigue or disengagement. Furthermore, we found a temporal effect of workload in the constant workload conditions, evidenced by increased fNIRS activation (HbO increase and HbR decrease), and mental fatigue measured by EEG (Delta power increase). Despite significant differences in cognitive load, we found little between-condition differences in physiological stress response as measured by ECG and EDA. At the same time, Easy yielded significantly higher participant ratings of valence, enjoyment, workload acceptability, and subjective performance, compared to Hard, indicating differing affective states. The combination of undistinguishable physiological stress and varying affective states suggests that participants experienced more of a state of eustress in Easy and distress in Hard conditions.